Dobre praktyki w zakresie ochrony dziecka w procesie resocjalizacji i readaptacji społecznej jego skazanych rodziców - Anna Dąbrowska; Justyna Kusztal (Problemy Wczesnej Edukacji)
The aim of the paper is to describe good practices in area of child’s protection according to the principle of child’s wellbeing in a crisis situation, more specifically – imprisonment of one of the parents. The paper presents assumptions and effects of an innovative social project implemented in cooperation with Puppet and Actor Theatre and Detention Center in Kielce (2015–2019). The programme’s goal was to support social re-adaptation process of convicted women and men by empowering family bonds, focusing especially on parent-child relations. The research methods are: analysis of legal acts, analysis of workshop contents and participant observation.